Translational potential of base-editing tools for gene therapy of monogenic diseases - Reshetnikov, Vasiliy V.; Chirinskaite, Angelina V.; Sopova, Julia V.; Ivanov, Roman A.; Leonova, Elena I. (Frontiers in Bioengineering and Biotechnology, 2022)
Millions of people worldwide have rare genetic diseases that are caused by various mutations in DNA sequence. Classic treatments of rare genetic diseases are often ineffective, and therefore great hopes are placed on gene-editing methods. A DNA base–editing system based on nCas9 (Cas9 with a nickase activity) or dCas9 (a catalytically inactive DNA-targeting Cas9 enzyme) enables editing without double-strand breaks. These tools are constantly being improved, which increases their potential usefulness for therapies. In this review, we describe the main types of base-editing systems and their application to the treatment of monogenic diseases in experiments in vitro and in vivo. Additionally, to understand the therapeutic potential of these systems, the advantages and disadvantages of base-editing systems are examined.